2020
DOI: 10.1186/s12872-020-01556-4
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain is associated with better outcomes in transcatheter aortic valve replacement

Abstract: Background: Parameters that mark the timing of left ventricular (LV) reverse remodeling following transcatheter aortic valve replacement (TAVR) are incompletely defined. This study aims to identify the dynamics of LV strain derived from speckle tracking echocardiography in a cohort of patients with severe aortic stenosis (AS) who underwent TAVR and its correlation with postprocedural outcomes. Methods: We selected 150 consecutive patients (82 ± 4 years old, STS score 6.4 ± 6.2) who underwent transfemoral TAVR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
2
10
0
6
Order By: Relevance
“…Our study shows gives impetus to the thought of intervening early in aortic valve disease by incorporating strain analysis in evaluation of patients for aortic valve replacement. Similar results were observed in many other studies [ 5 , 23 26 ]. Al-Rashid et al found that the global longitudinal strain (GLS) 1 week following TAVR was comparable to that at baseline (−15,9 ± 4.3 vs −16.8 ± 4.1; p = NS) but significantly improved at 3 months following TAVR (−15.9 ± 4.3% vs. −19.5 ± 3.5%; p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study shows gives impetus to the thought of intervening early in aortic valve disease by incorporating strain analysis in evaluation of patients for aortic valve replacement. Similar results were observed in many other studies [ 5 , 23 26 ]. Al-Rashid et al found that the global longitudinal strain (GLS) 1 week following TAVR was comparable to that at baseline (−15,9 ± 4.3 vs −16.8 ± 4.1; p = NS) but significantly improved at 3 months following TAVR (−15.9 ± 4.3% vs. −19.5 ± 3.5%; p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Al-Rashid et al found that the global longitudinal strain (GLS) 1 week following TAVR was comparable to that at baseline (−15,9 ± 4.3 vs −16.8 ± 4.1; p = NS) but significantly improved at 3 months following TAVR (−15.9 ± 4.3% vs. −19.5 ± 3.5%; p < 0.001). GLS improves at 3 months after TAVR, while LV ejection fraction does not show a substantial change, signalling an early recovery of LV longitudinal function after the intervention [ 23 ]. Lozano Granero VC et al found that between baseline and discharge, only a modest but statistically significant improvement in GLS (global longitudinal strain) could be seen (GLS% −14.6 ± 5.0 at baseline; −15.7 ± 5.1 at discharge following AVR, p = 0.0116) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LVGLS > − 14% had a reduced survival [ 8 , 25 ]. Furthermore, in a recent study Al-Rashid et al demonstrated that baseline LVGLS correlate significantly with postprocedural outcomes in 150 consecutive patients undergoing TAVR [ 26 ]. In addition, LVEF did not show any predictive value in terms of all-cause mortality, AV replacement or development of cardiac symptoms in the studies referred to above.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LVGLS >-14% had a reduced survival [8,25]. Furthermore, in a recent study Al-Rashid et al demonstrated that baseline LVGLS correlate signi cantly with postprocedural outcomes in 150 consecutive patients undergoing TAVR [26]. In addition, LVEF did not show any predictive value in terms of all-cause mortality, AV replacement or development of cardiac symptoms in the studies referred to above.…”
Section: Marwick Et Al Have Previously Demonstrated That Lvgls Is Anmentioning
confidence: 93%